Faktor-Faktor yang Berhubungan dengan Perilaku Remaja Jalanan terhadap Kesehatan Reproduksi di Yayasan Pembina Asuhan Bunda (YPAB) Kota Batam - Ulpawati, Ulpawati; Susanti, Susanti (stikes dharma husada bandung, 2021)
Adolescence is a transitional period between childhood and adulthood, starting at sexual maturity, namely between the ages of 10-12 years to 20 years, before young adulthood, street children are children who spend or use most of their time to carry out daily activities. the day on the road includes market environments, shops and other busy centers (Ministry of Social Affairs, 2016). The purpose of the investigation is for factors related to the behavior of street teenagers on health at the Batam City Bunda Asuhan Development Foundation (YPAB) in 2019. The research design used in this study was a survey analytic using a cross sectional approach. This research was conducted from May to September 2019 at YPAB 2019. The population in this study were 101 respondents with a sample size of 101 respondents, using purposive sampling technique. Collecting data using a questionnaire instrument and filled out by respondents. Data in tabular form and textual analysis using Chi-square. The results of statistical tests showed that 28 respondents (56.6%) had less knowledge, 27 people (54.0%) had negative attitudes, 34 people (68.0%) had the influence of peers and 31 people (62, 0%). There is a significant relationship between knowledge, peer attitudes and access to social media with the behavior of street teenagers on association health at YPAB Batam City in 2019.